RETRACTED: The role of key behavioral events in managing employee behavior at hotel-restaurant enterprises - Hakova Mira; Teslenko Tatyana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001